Isomerization Polymerization of the Phosphaalkene MesPCPh2: An Alternative Microstructure for Poly(methylenephosphine)s1. Issue 27 (5th June 2013) - Siu, Paul W.; Serin, Spencer C.; Krummenacher, Ivo; Hey, Thomas W.; Gates, Derek P.
<x xml:space="preserve">Abstract</x> Unique pathway: The radical‐initiated addition polymerization of MesP=CPh2 propagates through the ortho‐bound CH3 group of the Mes moiety after CH bond activation (see scheme, Mes=2, 4, 6‐trimethylphenyl, tht=tetrahydrothiophene, TEMPO=2, 2, 6, 6‐tetramethyl‐l‐piperidinoxyl). This unique isomerization polymerization mechanism contrasts the previously suggested head‐to‐tail enchainment typically observed for olefins.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>